The care of non-institutionalized ADL-dependent people in the Orcasitas neighborhood of Madrid (Spain) during the Covid-19 pandemic and its relationship with social inequalities, intergenerational dependency and survival - Martín Moreno, Vicente; Martínez Sanz, María Inmaculada; Martín Fernández, Amanda; Sánchez Rodríguez, Elena; Sánchez González, Irene; Herranz Hernando, Julia; Fernández Gallardo, Miriam; Recuero Vázquez, Miguel; Benítez Calderón, María Palma; Sevillano Fuentes, Eva; Pérez Rico, Elena; Calderón Jiménez, Laura; et al. (Frontiers in Public Health, 2024)
Background Mortality among people with dependency to perform basic activities of daily living (ADL) is higher than that of non-dependent people of the same age. Understanding the evolutionary course and factors involved in non-institutionalized ADL dependency, including the influence of the family structure that supports this population, would contribute to improved health planning. Methods A longitudinal study carried out in the ADL-dependent population of the Orcasitas neighborhood, Madrid (Spain), between June 2020, when the nationwide COVID-19 lockdown ended, and June 2023. A total of 127 patients participated in the study, 78.7% of whom were women and 21.3% were men. Risk analysis was performed via odds ratios (OR) and hazard ratios (HR). Survival analysis was performed using Cox regression. Results A total of 54.33% of the ADL-dependent persons did not live with their adult children and 45.67% did, being associated living independently with economic capacity and the married marital status but not with the dependency level. In women, being married increased the probability of living independently of their adult children (OR = 12.632; 95% CI = 3.312–48.178). Loss of mobility (OR = 0.398; 95% CI = 0.186–0.853), economic capacity of the dependent (HR = 0.596; 95% CI = 0.459–0.774), and living independently and having better economic capacity (HR = 0.471; 95% CI = 0.234–0.935) were associated with 3-year survival. Those who lived with their adult children had a worse autonomy profile and higher mortality (HR = 1.473; 95% CI = 1.072–2.024). Not being employed, not being married, and not owning a home were significantly associated with being an essential family caregiver. Caregivers were mostly women (OR = 1.794; 95% CI = 1.011–3.182). Conclusion Among ADL-dependent persons, economic capacity influenced the ability to living independently and affected survival after 3 years. Loss of mobility (wheelchair use) was a predictor of mortality. Social inequalities promote that adult children end up as essential family caregivers. This generates reverse dependency and maintains a vulnerability that is transmitted from generation to generation, perpetuating social and gender inequalities. Dependent parent care in this cohort maintained an archaic pattern in which the eldest daughter cared for her parents. This study made it possible to show that ADL dependence is accompanied by complex interrelationships that must be considered in socio-health planning.